1995
DOI: 10.1046/j.1471-4159.1995.64041605.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Acetylcholine and Glutamate on the Release of Arachidonic Acid from Cultured Striatal Neurons

Abstract: The activation of muscarinic and NMDA receptors by carbachol and NMDA, respectively, stimulated the release of [3H]arachidonic acid ([3H]AA) from cultured striatal neurons. Striking synergistic effects were observed when both agonists were coapplied. This synergistic response was suppressed by atropine or (5R, 10S)‐(+)‐5‐methyl‐10,11‐dihydro‐5H‐dibenzo[a,d]cyclohepten‐5,10‐imine hydrogen maleate and inhibited by magnesium. It was markedly reduced in the absence of external calcium and suppressed by mepacrine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 24 publications
2
10
1
Order By: Relevance
“…Significant progress has been made in the study of neuronal polarity (Dotti and Banker, 1991), G protein-coupled receptors (Vilchis et al, 2002;Morris et al, 2000), ion channel physiology (Sucher et al, 2000;Parak et al, 2001;Centonze et al, 2002) and inhibitory synaptic transmission (Kowalski et al, 1995) by using primary neuronal culture. Striatal neurons maintained in primary culture have been employed to study physiology of the NMDA receptors (Popp et al, 1998), opioid receptors (Vaysse et al, 1990), metabotropic glutamate receptors (Paolillo et al, 1998), and acetylcholine receptors (Tence et al, 1995 These preparations are particularly well suited for gene-transfer studies intended to manipulate electrical activity, since transduced neurons can be identified in the living state by the use of fluorescent reporter genes and their electrophysiological properties may be studied individually by patch clamp methods (Falk et al, 2003). In order to better extrapolate the results to the in vivo state, it is necessary to characterize the properties of cultured neurons under the specific growth and maintenance conditions utilized (Kessler, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been made in the study of neuronal polarity (Dotti and Banker, 1991), G protein-coupled receptors (Vilchis et al, 2002;Morris et al, 2000), ion channel physiology (Sucher et al, 2000;Parak et al, 2001;Centonze et al, 2002) and inhibitory synaptic transmission (Kowalski et al, 1995) by using primary neuronal culture. Striatal neurons maintained in primary culture have been employed to study physiology of the NMDA receptors (Popp et al, 1998), opioid receptors (Vaysse et al, 1990), metabotropic glutamate receptors (Paolillo et al, 1998), and acetylcholine receptors (Tence et al, 1995 These preparations are particularly well suited for gene-transfer studies intended to manipulate electrical activity, since transduced neurons can be identified in the living state by the use of fluorescent reporter genes and their electrophysiological properties may be studied individually by patch clamp methods (Falk et al, 2003). In order to better extrapolate the results to the in vivo state, it is necessary to characterize the properties of cultured neurons under the specific growth and maintenance conditions utilized (Kessler, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, according to previous studies, AA is a potent inhibitor of astrocyte GJC (18)(19)(20). In addition, as shown in neuronal cultures from the mouse striatum, this unsaturated fatty acid is released after stimulation of NMDA receptors (27), and a synergistic response is observed under costimulation of NMDA and muscarinic receptors (15). Therefore, the evoked AA release was investigated in our different models of rat striatal cultures.…”
Section: Nmda and Muscarinic Receptor Costimulation Induces The Releamentioning
confidence: 89%
“…Because cultured astrocytes do not express N-methyl-D-asparte (NMDA) receptors (14), cocultures of neurons and astrocytes provide an appropriate model to address this question by selectively stimulating neurons. Interestingly, in striatal neurons, several biochemical and electrophysiological responses evoked by NMDA are enhanced by acetylcholine (Ach) through the stimulation of muscarinic receptors (15,16). This could partly account for the modulatory role of cholinergic interneurons on the activity of efferent striatal neurons (see ref.…”
mentioning
confidence: 99%
“…Neurotransmitters affect PUFA turnover, as PLA 2 is activated by multiple receptor types--dopamine D 2 (Vial and Piomelli, 1995), serotonin 5-HT 2 (Berg et al, 1996), glutamate (Tence et al, 1995), and muscarinic acetylcholine (Jones et al, 1996)--to liberate fatty acids from the sn -2 position of phospholipids. In turn, PUFAs also regulate the activity, mRNA expression, and protein levels of multiple PLA 2 isoforms (Downes and Currie, 1998; Lister et al, 1988; Rao et al, 2007a).…”
Section: Brain Pufasmentioning
confidence: 99%